2012
DOI: 10.1021/ic300357d
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Reversible Electrode Reaction of Na1–xNi0.5Mn0.5O2 for a Rechargeable Sodium-Ion Battery

Abstract: Layered NaNi(0.5)Mn(0.5)O(2) (space group: R ̅3m), having an O3-type (α-NaFeO(2) type) structure according to the Delmas' notation, is prepared by a solid-state method. The electrochemical reactivity of NaNi(0.5)Mn(0.5)O(2) is examined in an aprotic sodium cell at room temperature. The NaNi(0.5)Mn(0.5)O(2) electrodes can deliver ca. 105-125 mAh g(-1) at rates of 240-4.8 mA g(-1) in the voltage range of 2.2-3.8 V and show 75% of the initial reversible capacity after 50 charge/discharge cycling tests. In the vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

37
567
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 649 publications
(651 citation statements)
references
References 46 publications
37
567
3
3
Order By: Relevance
“…Recently, several layered Na x MO 2 (M: 3d transition metals, TMs) compounds have been proposed as positive electrode materials for sodium-ion batteries [42][43][44][45][46][47][48][49][50][51][52] . It has also been demonstrated that P2-type materials show better storage performance than that of O3-type materials (Note that the notations of P2 and O3 were defined by Delmas et al 53 , they refer to different ways of the stacking of the oxygen layer, for example, ABBA for P2, ABCABC for O3 and so on) 46 .…”
mentioning
confidence: 99%
“…Recently, several layered Na x MO 2 (M: 3d transition metals, TMs) compounds have been proposed as positive electrode materials for sodium-ion batteries [42][43][44][45][46][47][48][49][50][51][52] . It has also been demonstrated that P2-type materials show better storage performance than that of O3-type materials (Note that the notations of P2 and O3 were defined by Delmas et al 53 , they refer to different ways of the stacking of the oxygen layer, for example, ABBA for P2, ABCABC for O3 and so on) 46 .…”
mentioning
confidence: 99%
“…Similar to their Li counterparts,1 though sodium‐based system has similar electrochemical reaction characteristics compared to lithium‐based one, the larger ionic radius for sodium ion cause sluggish kinetics and volume change during Na storage, leading to lower capacity, poor cycling and rate properties of the Na storage materials. Recently, major efforts have been devoted to promote the electrochemical performance of Na storage materials, for example, Na x MO 2 ,2, 3, 4, 5, 6, 7, 8, 9, 10 polyanionic framework compounds,11, 12, 13, 14, 15, 16, 17, 18, 19 hexacyanoferrate,20, 21, 22, 23, 24, 25, 26, 27 for the cathode materials, and hard carbons,28, 29, 30, 31, 32, 33 alloys,34, 35, 36, 37, 38, 39, 40, 41 oxides,42, 43 sulfides37, 44, 45, 46 for the anode materials.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several types of insertion materials have been introduced as cathode materials for sodium-ion batteries (SIBs) including P2-types [9][10][11][12][13][14][15][16] , O3-types [17][18][19][20][21][22][23][24][25][26][27][28][29] , pyrophosphates [30][31][32] and organo-compounds [33][34][35] . Owing to the large ionic size of Na þ ions (1.02 Å), their insertion into a spinel framework does not readily occur.…”
mentioning
confidence: 99%
“…In contrast, two-dimensional layer structures do favour the insertion of Na þ ions into their structures. Among these, P2-(refs 9-16) and O3-types [17][18][19][20][21][22][23][24][25][26][27][28][29] , which are classified by their sequence of oxygen stacking, are of interest because of their large reversible capacities. For layer-structured compounds, the P2-type usually stabilizes into Na-deficient compositions such as Na 2/3 MO 2 (M: Ni, Co, Mn, Fe and so on).…”
mentioning
confidence: 99%